Exchange Market Pressures and Speculative Capital Flows in Selected European Countries - Pazarbasioglu, Ceyla (IMF Working Papers; Working Paper ;, 1994)
This paper estimates a speculative attack model of currency crises in an attempt to identify the roles of macroeconomic fundamentals and speculative market pressures in the recent crisis, as well as earlier devaluations in adjustable fixed exchange rate systems in the European currency markets. For a sample of five countries, including Denmark, Ireland, Spain, Norway, and Sweden, our empirical analyses show that both economic fundamentals and speculative factors have a significant influence on the probability of devaluations. The recent experience in the European foreign exchange markets suggests that the latest realignments are mainly the result of foreign exchange market tensions amidst the growing conflict between the needs of the domestic economies and the policies needed to maintain fixed exchange rates. Our results confirm that regardless of the source of the deterioration in economic conditions, market participants perceived the existing parities of the currencies in these five countries as inconsistent with their underlying economic fundamentals, thus effectively bringing about either a realignment or a modification of the exchange arrangement.